2017
DOI: 10.17957/tpmj/17.4047
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Humerus Fractures; Radiological and Functional Outcome as Treated With the Philos Plating System, at a Tertiary Care Centre in Karachi, Pakistan.

Abstract: ABSTRACT… Objectives:The aim of our study is to study the radiological and functional outcome of proximal humerus fractures treated via open reduction and internal fixation using the proximal humerus internal locking system or PHILOS. Study Design: Case series study. Period 05 years duration from January 2011 to December 2015. Setting: Large tertiary care centre in Karachi, Pakistan. Materials and methods: The study population consisted of n=50 patients all of whom underwent open reduction and internal fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The functional outcome of the PHILOS in displaced proximal humeral fracture had 76% favorable and 24% unfavorable functional outcome [14]. Similar results were observed in another study conducted by Jabbar FA, et al [12] in which the study population consisted of n= 50 patients of which n= 35 were males and n= 15 were females having a mean age of 38-50 years. The mean duration of follow up was 24 months.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The functional outcome of the PHILOS in displaced proximal humeral fracture had 76% favorable and 24% unfavorable functional outcome [14]. Similar results were observed in another study conducted by Jabbar FA, et al [12] in which the study population consisted of n= 50 patients of which n= 35 were males and n= 15 were females having a mean age of 38-50 years. The mean duration of follow up was 24 months.…”
Section: Discussionsupporting
confidence: 78%
“…This descriptive case series study was conducted in Akber Medical Centre Ramdas Bazaar Peshawar Pakistan from August 2018 to February 2022 on total 71 patients of either gender of age more than 15 years. Using WHO sample size calculator, keeping 76% [12] prevalence of favorable functional outcome of the PHILOS plating measured based on Constant and Murley scoring system, 95% confidence level and 10% margin of error the sample size was 71. Non-probability Consecutive sampling Technique was used in our study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, Excellent functional outcome was seen in 21.9%, good 36%, fair 33.3% and poor was 8.8%. In a study by Jabbar FA, et al has shown that frequency of excellent functional outcome was 54%, good 24%, fair 14% and poor was 8% after proximal humerus fracture fixation using PHILOS system [9]. In another study by Rao NN, et al has shown that frequency of excellent functional outcome was 4%, good 44%, fair 44% and poor was 8% after proximal humerus fracture fixation using PHILOS system [10].…”
Section: Discussionmentioning
confidence: 99%
“…PHILOS plate provides rigid fixation, more angular stability and early mobilization. There is variability in results when PHILOS system is used in different populations as shown in above studies [9,10]. Therefore further evidence is needed to evaluate the functional outcomes of proximal humeral internal locking system in treatment of proximal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%